The combined medical/PhD degree: a global survey of physician-scientist training programmes - Alamri, Yassar (Clin Med (Lond), 2016)
Typically lasting 7–9 years, medical-scientist training programmes (MSTPs) allow students a unique opportunity to simultaneously intercalate medical (MBBS, MBChB or MD) and research (PhD) degrees. The nature of both degrees means that the combined programme is arduous, and selection is often restricted to a few highly motivated students. Despite the many successes of MSTPs, enthusiasm about MSTPs and the number of intercalating students, at least in some countries, appear to be diminishing. In this review, I shed light on MSTPs around the world, highlight the plethora of successes such programmes have had and provide insights on the setbacks experienced and solutions offered, with the aim of reigniting interest in these programmes.